Gender Differences in Fecal Immunochemical Test Performance for Early Detection of Colorectal Neoplasia - Kapidzic, A.; van der Meulen, M.; Hol, L.; van Roon, A.; Looman, C.; Lansdorp_Vogelaar, Iris; van Ballegooijen, M.; van Vuuren, A.; Reijerink, J.; van Leerdam, M.; Kuipers, E. (W.B. Saunders Co, 2015)
Background & Aims: Fecal immunochemical tests (FITs) are used widely in colorectal cancer screening. Programs use the same fecal hemoglobin threshold for colonoscopy referral for men and women, but it is unclear whether FIT performs equally in both sexes. We therefore assessed FIT performance in men and women. Methods: A prospective cohort study was performed, in which a total of 10,008 average-risk subjects (age, 50-74 y) were invited for first-round screening and 8316 average-risk subjects (age, 51-74 y) were invited for second-round screening with a single FIT. Subjects with a hemoglobin (Hb) level of 10 µg hemoglobin (Hb)/g (or =50 ng/mL) feces or higher were referred for colonoscopy. The test characteristics were assessed by sex for a range of FIT cut-off values. Results: In total, 59.8% of men and 64.6% of women participated in the first round (. P < .001). At a cut-off level of 10 µg Hb/g feces, the positivity rate was significantly higher among men (10.7%) compared with women (6.3%; P < .001) in the first round. The detection rate of advanced neoplasia was 4.4% for men and 2.2% for women (. P < .001) in the first round. The positive predictive value for advanced neoplasia in the first round was 42% for men and 37% for women (. P = .265). A significantly higher false-positive rate in men (6.3%) than in women (4.1%; P < .001) was found. Similar differences in these test characteristics were seen in the second round. Conclusions: At a cut-off level of 10 µg Hb/g feces the FIT positivity rate was higher in men, reflected by both a higher detection rate and a higher false-positive rate. The use of the same cut-off value in men and women in FIT screening is recommended based on equal test performance in terms of positive predictive value.